Learning environment of university business studies classrooms: Its assessment, determinants and effects on student outcome - Skordi, Panayiotis George (Curtin University, 2014)
For a sample of 375 students from 12 business statistics classes in Southern Californian universities, I assessed the classroom learning environment and investigated its determinants and effects. Three determinants (sex, ethnicity and age) of classroom environment and student outcomes (anxiety, attitudes and achievement) were investigated along with its effects on these student outcomes. The findings could guide statistics instructors in how to change their classrooms to improve student outcomes and to accommodate between-student differences.